Chita The Chimpanzee - Mbaegbu Nneka (Macmillian Nigeria, 1992)
Chita was a chimpanzee from the jungles of Nairobi, Kenya. How did it become one of Mr. Freddie's household and how did they part ways. Find out as you read along
Keywords: Juvenile Fiction / Animal